From caterpillar to butterfly - Hewitt, Sally (Irvine, CA : QEB Pub. Inc., 2004)
Describes different stages in the life of a butterfly as it changes from egg to caterpillar, caterpillar to chrysalis, and chrysalis to adult butterfly.
2.8
K-3
Keywords: Butterflies -- Juvenile literature; Butterflies -- Metamorphosis -- Juvenile literature; Butterflies; Caterpillars; Metamorphosis; Butterflies; Caterpillars; Metamorphosis; Metamorphosis; Butterflies; Caterpillars